The exploration of genetic characteristics of Madura cattle - Hartatik, Tety; Widi, T.S. Mastuti; Ismaya, Ismaya; Widayati, Diah Tri; Baliarti, Endang (2010)
The research was conducted to observe the exterior characteristics and performance of Madura cattle based on qualitative and quantitative traits. This research was conducted in Pamekasan, Sumenep, and Sapudi Island, Madura, East Java province. Two groups of Sonok calf and Sonok cow in total number of 157 cattle samples were used for observation of exterior characteristics. The body measurements and performance data were obtained from 203 Madura cattle. The result showed that Sonok calf and Sonok cow have different exterior characteristics. The Sonok cows showed several changes on exterior characteristics from those of Sonok calves, such as appearing of the chest fat and back line, size of hump, the lappet size, and the colors surrounding eyes, nose and mouth. The body measurements of 2-3 y old of Sonok cattle were higher than that of Madura cattle in Sumenep and in Sapudi Island. In example, girths of chest of those cattle are 163.19 ± 9.87 cm, 138.44 ± 18.36 cm and 148.88 ± 10.18 cm, respectively. More interestingly, the Sonok cattle in the same area showed the improvement of body measurements compare with the pervious results in 1992 (girth of chest 158.19±10.88 cm). Performance ofMadura cattle such as weaning age, first age ofmating, first age of calving were 5.75 ± 0.78 mo, 19.571 ± 0.53 mo, and 30.00 ± 0.00 mo, respectively. The estimation of body weight in those phase were 151.58 ± 36.98 kg, 240.00 ± 45.96 kg, and 251.08 ± 68.33 kg, respectively. Based on this research, Sonok calf and Sonok cow had spesific characteristics. Generaly body measurements and performance of Sonok cattle was better than Madura cattle in general. Therefore, we suggest that the population of Sonok cattle could be improved in order to get high quality local cattle in Madura island. Key words: exterior characteristics, body measurements, Sonok calf, Sonok cow, Madura cattle